If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -2(8x + -7) = 22 Reorder the terms: 18 + -2(-7 + 8x) = 22 18 + (-7 * -2 + 8x * -2) = 22 18 + (14 + -16x) = 22 Combine like terms: 18 + 14 = 32 32 + -16x = 22 Solving 32 + -16x = 22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-32' to each side of the equation. 32 + -32 + -16x = 22 + -32 Combine like terms: 32 + -32 = 0 0 + -16x = 22 + -32 -16x = 22 + -32 Combine like terms: 22 + -32 = -10 -16x = -10 Divide each side by '-16'. x = 0.625 Simplifying x = 0.625
| 5t-1=-46 | | 6k+2=3k+5k | | 10x^2+10x+3=19-4x^2+16 | | X-5+2x-4=12 | | 6.09x^2+4.57x-8.86=0 | | (7x-3)(2x+9)=0 | | 7(-6+3z)=42 | | x^3=79 | | 5t^2-10t-50=0 | | 27c+5-25c=49 | | 9a+5a+7a+8a= | | 5(4x-2)=2(3+6x) | | 15x-2x=-7x | | 42x-210=27x | | 3+10a-8=15 | | 6x-9+2x=5+8x-13 | | 2+x+y=x+5 | | 2x-2+2y=2+x+y | | 5r^2-19r-4= | | -3p+2+4p=-5 | | +65+(x-5)=180 | | x^4+15x-30= | | 7+20x=4(5x+3) | | 4y+9=3y-3 | | +65+(x-5)=60 | | 1.01*0.231= | | 6=-0.2r | | 5x+6=2x+13 | | 3x+2=3+x+3 | | 7y-14-4y+9=0 | | T=hp+b | | 3x+2=3+x-3 |